An uncommon case of a pyelogenic cyst containing two calculi - Montatore, Manuela; Eusebi, Laura; Masino, Federica; Balbino, Marina; Muscatella, Gianmichele; Sciacqua, Alessio; Gifuni, Rossella; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: This case describes a rare and complicated pyelogenic cyst in a 32-year-old female who presented with intermittent right flank pain and mild dysuria for six months. Although pyelogenic cysts are typically asymptomatic, the presence of lithiasis significantly complicates both the diagnosis and management.Methods: Imaging studies, including ultrasound and contrast-enhanced CT, revealed a calyceal diverticulum located in the mid-calyceal region of the right kidney.Results: This cyst is complicated, as it contains two calculi and communicates with the renal collecting system.Conclusions: Conservative treatment may be effective for less symptomatic patients; however, recurring symptoms or complications may demand procedures such as lithotripsy or surgical resection. This case underscores the rarity of such presentations and highlights the crucial role of radiological evaluation in guiding clinical management.